Application of Surveillance and Monitoring in the Mature Waterflood Field - Muhammad Iqbal Arrasyid; Rinaldy Dalimi (Jurnal Indonesia Sosial Teknologi, 2024)
Waterflood is one of the keys in maintaining reservoir health and carrying out oil recovery in the secondary stage. In its development, the implementation of surveillance and monitoring activities is carried out to monitor waterflood performance both from the production and injection sides on a regular basis to maximize production optimization. However, there are many challenges that must be faced in developing waterflood, some of which are maintaining the Voidage Replacement Ratio (VRR) and the production of unexpected water. Therefore, a simpler and easy-to-apply surveillance and monitoring approach is needed. This paper describes how the application of waterflood surveillance and monitoring principles and practices is carried out in carrying out the oil recovery process and monitoring reservoir health. The reservoir health monitoring process includes several aspects such as Voidage Replacement Ratio (VRR) and Water-Oil Ratio (WOR), as well as identification of areas of interest of accumulated oil through the Production Attribute approach. The application is carried out on Field 'X' which has a typical production with a fairly high water cut. This approach was successfully applied to Field 'X' and gave the results of the approach that was quite ideal to be applied